2001
DOI: 10.1038/sj.onc.1204923
|View full text |Cite
|
Sign up to set email alerts
|

The specific activation of gadd45 following UVB radiation requires the POU family gene product N-oct3 in human melanoma cells

Abstract: Here we report the speci®c regulation of gadd45 expression in human melanoma cell lines following UVB radiation. This solar wavelength is likely to be involved in melanoma aetiology. We have previously shown that gadd45 expression is strongly enhanced in a p53-independent manner following UVB irradiation, unlike the other p53 target genes studied. Furthermore, gadd45 is speci®cally activated in melanocytes since its induction in response to UVB, is not observed in other skin cells such as keratinocytes or ®bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 42 publications
0
24
1
Order By: Relevance
“…The incidence of nonmelanoma skin cancer, comprising of basal-and squamous-cell carcinoma, continues to increase in the United States, and solar UV, particularly its UVB (280-320 nm) spectrum, is the primary cause of these cancers and other cutaneous pathologies in the human population, more so in Caucasian individuals (Mukhtar and Elmets, 1996;Ananthaswamy et al, 1997;Greenlee et al, 2000;Jemal et al, 2000;de Gruijl, 2002). Exposure of mammalian skin to UV radiation alter cellular function via DNA damage (Vink et al, 1997;Katiyar et al, 2000), generation of reactive oxygen species (ROS) (Scharffetter-Kochanek et al, 1997;Katiyar et al, 2001a, b), activation and phosphorylation of mitogen-activated protein kinases (MAPKs), nuclear factor kappa B (NF-kB), and other signaling events (Iordanov et al, 1997;Chen et al, 1999;Katiyar and Mukhtar, 2001;Lefort et al, 2001;Bachelor et al, 2002;Hildesheim et al, 2002;Afaq et al, 2003a), and acts both as a tumor initiator and tumor promoter in animal models (Gensler and Welch, 1992;Katiyar et al, 1997). The UVB-induced activation of signal transduction pathways that control the expression of genes is responsible for its tumor-promoting effects (Huang et al, 1996;Chen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of nonmelanoma skin cancer, comprising of basal-and squamous-cell carcinoma, continues to increase in the United States, and solar UV, particularly its UVB (280-320 nm) spectrum, is the primary cause of these cancers and other cutaneous pathologies in the human population, more so in Caucasian individuals (Mukhtar and Elmets, 1996;Ananthaswamy et al, 1997;Greenlee et al, 2000;Jemal et al, 2000;de Gruijl, 2002). Exposure of mammalian skin to UV radiation alter cellular function via DNA damage (Vink et al, 1997;Katiyar et al, 2000), generation of reactive oxygen species (ROS) (Scharffetter-Kochanek et al, 1997;Katiyar et al, 2001a, b), activation and phosphorylation of mitogen-activated protein kinases (MAPKs), nuclear factor kappa B (NF-kB), and other signaling events (Iordanov et al, 1997;Chen et al, 1999;Katiyar and Mukhtar, 2001;Lefort et al, 2001;Bachelor et al, 2002;Hildesheim et al, 2002;Afaq et al, 2003a), and acts both as a tumor initiator and tumor promoter in animal models (Gensler and Welch, 1992;Katiyar et al, 1997). The UVB-induced activation of signal transduction pathways that control the expression of genes is responsible for its tumor-promoting effects (Huang et al, 1996;Chen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have shown that solar UV radiation elicits many adverse biological effects in the skin, including hyperpigmentation, erythema, photoaging, immunosuppression, and cancer (Goihman-Yahr, 1996;Ananthaswamy et al, 1997;DeGruijil, 1999;Afaq and Mukhtar, 2001). UV radiation to mammalian skin is known to alter cellular function via DNA damage (Eller et al, 1997;Vink et al, 1997;Katiyar et al, 2000), generation of reactive oxygen species (ROS) (Morita et al, 1997;Scharffetter-Kochanek et al, 1997;Katiyar et al, 2001a, b), and the resultant alterations in a variety of signaling events (Gilchrest et al, 1996;Knebel et al, 1996;Rosette and Karin, 1996;Iordanov et al, 1997;Chen et al, 1999;Lefort et al, 2001;Pfundt et al, 2001). The endogenous antioxidant capacity of the skin is a major determinant in its response to UV-induced oxidative stress-mediated skin damage.…”
mentioning
confidence: 99%
“…The genes encoding the α, β and γ isoforms of Gadd45 are respectively located at 1p31.2, 19p13.3 and 9q22.1 in the human genome, and they have different promoters and introns (Kastan et al, 1992;Jung et al, 2000;Lefort et al, 2001;Furukawa-Hibi et al, 2002;Thyss et al, 2005). Each gene is induced by a distinct subset of environmental and physiological stresses (Liebermann and Hoffman, 2007).…”
Section: Introductionmentioning
confidence: 99%